(untitled) (Journal of Geography and Environmental Management, 2020)
The article considers the compilation of a short-term forecast of mudflow forming sediments using numerical forecasting methods, since this factor is an important condition for the preparation of rainfall mudflow forecasts, it is necessary to determine the degree of accuracy and efficiency of the methodology by which the forecast was made. Accurate and reliable forecasts are the guarantor of increasing the effectiveness of protecting the population. To forecast rainfall, the US Weather Bureau model was used and the results of forecasting rainfall and debris flows of storm origin for Ile-Alatau weather stations are shown. The results of a short-term forecast of precipitation with a lead time of 1 day and with a justification of 83% were also illustrated. For forecasting mudflows using well-known techniques, the accuracy of forecasts for the adopted period was unsatisfactory. This attempt should continue, since the series (daily data for the mudflow hazard period) that were used in this work cover only 2 years